Etiology of Delayed Inflammatory Reaction Induced by Hyaluronic Acid Filler - Lee, Won; Shah-Desai, Sabrina; Rho, Nark-Kyoung; Cho, Jeongmok (Archives of Plastic Surgery, 2024)
The etiology and pathophysiology of delayed inflammatory reactions caused by hyaluronic acid fillers have not yet been elucidated. Previous studies have suggested that the etiology can be attributed to the hyaluronic acid filler itself, patient's immunological status, infection, and injection technique. Hyaluronic acid fillers are composed of high-molecular weight hyaluronic acids that are chemically cross-linked using substances such as 1,4-butanediol diglycidyl ether (BDDE). The mechanism by which BDDE cross-links the two hyaluronic acid disaccharides is still unclear and it may exist as a fully reacted cross-linker, pendant cross-linker, deactivated cross-linker, and residual cross-linker. The hyaluronic acid filler also contains impurities such as silicone oil and aluminum during the manufacturing process. Impurities can induce a foreign body reaction when the hyaluronic acid filler is injected into the body. Aseptic hyaluronic acid filler injections should be performed while considering the possibility of biofilm formation or delayed inflammatory reaction. Delayed inflammatory reactions tend to occur when patients experience flu-like illnesses; thus, the patient's immunological status plays an important role in delayed inflammatory reactions. Large-bolus hyaluronic acid filler injections can induce foreign body reactions and carry a relatively high risk of granuloma formation.
Keywords: hyaluronic acid filler; delayed inflammatory reaction; filler complication; delayed hypersensitivity